notary's responsibility in making a deed of grant that is cancelled due to legal defects - Fahmi, Ismail; Hasana, Dahniarti (Jurnal Konstatering, 2026)
This study analyzes the cancellation of a deed of gift declared legally flawed and its implications for the position and accountability of a Notary, particularly when the Notary holding the protocol is also sued in an inheritance dispute. The study uses a normative legal research method with a statutory, conceptual, and case approach through a study of Decision Number 2193 K/Pdt/2018. Data are sourced from secondary legal materials obtained through literature studies and analyzed descriptively-analystically. The results of the study indicate that the withdrawal of the Notary holding the protocol as a co-defendant is administrative and pragmatic, primarily for the purposes of proving the minutes of the deed and avoiding the exception of lack of parties. The Notary's liability for the cancellation of a deed of gift is limited and can only be requested if there is proven error or negligence in fulfilling the formal obligations of the position. Legal protection for heirs is realized through the cancellation of a legally flawed deed of gift, the restoration of the status of the object of the gift as a boedel heir, and the strengthening of the precedent of caution in making a deed of gift so as not to eliminate inheritance rights.